2021
DOI: 10.3390/su131910617
|View full text |Cite
|
Sign up to set email alerts
|

A Systematic Literature Review of Inclusive Climate Change Adaption

Abstract: Inclusive approaches have been applied in many areas, including human resources, international development, urban planning, and innovation. This paper is a systematic literature review to describe the usage trends, scope, and nature of the inclusive approach in the climate change adaptation (CCA) context. We developed search algorithms, explicit selection criteria, and a coding questionnaire, which we used to review a total of 106 peer-reviewed articles, 145 grey literature documents, and 67 national communica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 113 publications
1
7
0
Order By: Relevance
“…There is an offset to be made here. Although limiting a systematic review to peer-reviewed literature has a high potential towards bias, because important trends and insights could be missed [ 11 , 13 ], a small sample size may be deemed appropriate because most systematic reviews of existing literature rarely exceed 100 documents [ 34 ]. In other words, we share a fact that can be found in the systematic analysis conducted by Vasileiou et al [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…There is an offset to be made here. Although limiting a systematic review to peer-reviewed literature has a high potential towards bias, because important trends and insights could be missed [ 11 , 13 ], a small sample size may be deemed appropriate because most systematic reviews of existing literature rarely exceed 100 documents [ 34 ]. In other words, we share a fact that can be found in the systematic analysis conducted by Vasileiou et al [ 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…This implies that only a limited number of (non)systematic reviews have been conducted on conceptual frameworks applied to evaluate these impacts in urban areas, and therefore implies the difficulty of obtaining the main directions and key methods in closely related areas. In parallel, Pham and Saner [ 11 ] point out that the notion of inclusiveness has been underrepresented with respect to both sentient nonhuman animals and the interests of future generations, and emphasize the need for conceptual and empirical research because of the lack of reviews focused on the issue of inclusive climate adaptation.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Peripheral actors include (1) academics with deep disciplinary knowledge with an inclination toward interdisciplinary collaboration, (2) citizens who are often underrepresented or excluded from expert convergence processes (Fischer, 2000), (3) future actors for whom knowledge cannot be defined nor can individual actors be delineated, and (4) ecosystem agents and in particular sentient non-human animals (Pham and Saner, 2021). Actor types 3 and 4 often require proxies: experts on sustainability, datasets, representatives of civil society, and even scientists who can make informed statements on what may benefit or burden nature and future generations.…”
Section: Peripheral Actorsmentioning
confidence: 99%
“…In a forthcoming scoping review, authors found that 40% of adaptation and equity papers were conceptual in nature, as opposed to empirical and data-driven (11). These reviews, in combination with reviews of specific types of adaptation strategies (18,19), point to the importance of scholarship that clearly investigates the 'on the ground' equity implications of climate adaptation. Such scholarship is needed in combination with broader conceptual work to reach a nuanced and evidence-based scientific understanding of adaptation and equity interactions.…”
Section: Conceptual Approaches To Studying Equity and Justice In Clim...mentioning
confidence: 99%